Effects of culture conditions on the developmental programme of mouse blastocysts - Sellens, M H; Sherman, M I (Journal of embryology and experimental morphology, 1980)
We have investigated the developmental potential of mouse blastocysts cultured under a variety of conditions. A number of parameters were used as criteria for development and differentiation, namely hatching of blastocysts from the zona pellucida and their adhesion to the substratum, outgrowth and polyploidization of trophoblast cells, increase in cell number, protein content, beta-glucuronidase activity, appearance of lactate dehydrogenase A subunits, plasminogen activator production, and delta 5,3 beta hydroxysteroid dehydrogenase activity. Under optimal culture conditions, embryos grew relatively rapidly and expressed all the differentiative markers for which they were tested. Under less supportive conditions, the production of the markers was usually reduced quantitatively; the expression of some markers could also be considerably delayed or even totally prevented. In fact, embryos cultured in the least nutritive medium (one designed to support development only through pre-implantation stages) appeared to be in a state of metabolic quiescence closely resembling that of blastocysts in ovariectomy-induced delay. Overall, the results of our investigations lead us to propose that the expression of each of the aforementioned markers is probably under independent control and subject to intrinsic programming. Finally, the observation that some markers are produced by embryos in suboptimal media whereas others are not, suggests that the minimum metabolic level necessary for expression varies from one marker to another.